Litter and Soil Carbon Stock in Cultivated and Natural Area of Intergrated Forest for Conservation Education of Wan Abdul Rachman Great Forest Park - Leoni Dellta Ellannia; Agus Setiawan; Ainin Niswati (JOURNAL OF TROPICAL SOILS, 2016)
Intergrated Forest for Conservation Education of Wan Abdul Rachman (IFCE WAR) Great Forest Park is a conservation forest zone which has natural area and cultivated area.  The natural area in Wan Abdul Rachman Great Forest Park consists of secondary forest, whereas the cultivated area consists of agroforestry with cacao plants and agroforestry with coffee plants. The different land use in both areas caused the difference in carbon sink specifically in litter and soil. The research was aimed to study the difference of litter and soil carbon stock in natural and cultivated area in IFCE WAR Great Forest Park.  The observation plots included in the current study was determined using purposive sampling method. The research was conducted in June until August 2015. Data was analyzed using analysis of variance and continued with honestly significant difference test. The results showed that there was no difference of litter carbon stock in cultivated area and natural area in IFCE WAR Great Forest Park, whereas the soil carbon stock in natural area was higher than that in cultivated area.